The Relevance of Standard Costing and Variance Analysis in Global Industries Today - Teoh Choon Hung; Jaya Kumar Shanmugam (East Asian Journal of Multidisciplinary Research, 2023)
Standard Costing and variance analysis are a set of management accounting tools that assist industries in controlling the cost of production. It involved the establishment of a cost standard that is required, and the standard cost was applied for comparison to the product’s actual cost. This article aimed to critically explore and assess the applicability of using standard costing and variance analysis as management accounting tools in today's varied worldwide industries. By compiling the findings from various scholars and researchers, this article primarily examines what standard costing methods and variance analysis are, as well as their advantages, limitations, and usefulness. Moreover, the proposed research framework on the motivation of industries in standard costing technique adoption and recommendations were added for future research purposes in this article. As a result, the article successfully concluded that standard costing techniques and variance analysis were relevant and crucial management accounting tools for industries today.